TRADISI SESEMAH BAGI MASYARAKAT MELAYU DI KECAMATAN KUBU BABUSSALAM ROKAN HILIR - Muhammad Azahari; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted in the District of Kubu Babussalam Rokan Hilir with the aim of explaining the sesemah Tradition for the Malay Community in the District of Kubu Babussalam Rokan Hilir and explaining the function of sesemah for the Malay Community in the Kubu Babussalam Rokan Hilir. This study uses descriptive qualitative research methods. Data collection was carried out using in-depth interview techniques, direct observation and documentation. The results of the analysis show that the divided sesemah tradition is carried out in high tide conditions, as well as an unspecified time for small sesemah. In the sesemah tradition there are many values of life that must be taught to the younger generation today. The sesemah tradition also teaches humans not to forget to give alms when they get something or a favor. sesemah tradition also invites humans to always live in harmony with nature Keywords: Tradition, sesemah Malay Society.